Critical dialogues in higher education - Algert, Nance T.; Gill, Clare A. (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"This book is designed to support individuals, particularly in higher education settings, gain knowledge and skills related to critical dialogues that support effective conflict management. Higher education institutions and its stakeholders such as faculty, staff, students, and administrators are often perceived for their proclivity to foster debate. This book is not about how to facilitate debate, but rather, dialogue, which if managed well, can lead to positive growth, learning outcomes, and increased productivity. Dialogue as a method for effective conflict management is an underutilized method of communication. Contents of the book include modules that address communication skills, conflict management styles, working in small groups or teams, how to facilitate change, and research-based resources and references for conflict management"-- Provided by publisher.
Keywords: College teachers -- Professional relationships -- United States.; College administrators -- Professional relationships -- United States.; College environment -- United States.; Conflict management -- United States.; Organizational behavior -- United States.; Communication in education -- United States.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books